Pengaruh brand image dan brand trust sebagai variabel intervening dalam memilih universitas - Juliana Juliana; Johan Johan (STIE Perbanas Surabaya, 2019)
The purpose of this research is to analyze the effect of brand image on purchase intention in selecting a desired University, the effect of brand image on brand trust and the effect of brand trust as the intervening variable on purchase intention when selecting the desired University. The data collection is done by having a survey using questionnaires sent to 100 students in three different high schools who are in their senior year. This research is using quantitative approach with PLS-SEM method using the assistance of SmartPLS 3.2.7 software to evaluate the outer model and the inner model. The result shows that brand image and brand trust as the intervening variable have significant effect on purchase intention when selecting the desired University by students.